What should be the PSA threshold value? 2.5 or 4 ng/mL? - Ediz, Caner; Cimen, Serhan; Akan, Serkan; Temel, Muhammed Cihan; Yilmaz, Omer; Koksal, Ozlem (International Journal of Research in Medical Sciences, 2019)
Background: In this study, author aimed to detect of threshold value of prostate-specific antigen (PSA) to distinguish malignant or benign prostatic lesions in PSA evaluation. Methods: A total of 61 patients underwent TRUSBP due to high PSA values (2.5-4 ng/mL) at the clinic between 2012-2017. Digital rectal examinations of all patients were normal. Cases with PSA elevation were divided into groups according to the pathology by benign (group 1) or malign (group 2). Author evaluated the predictive factors with the exception of digital rectal examination findings in two groups. Results: Benign prostate hyperplasia was detected in 35 patients (57.4%) and prostate adenocarcinoma was detected in 26 patients (42.6%). The patient’s age, tPSA, fPSA and PSA density were 62.07 years, 3.55 ng/mL, 0.65 ng/mL and 0.09 ng/ml2 in group 1 and 58.54 years, 3.55 ng/mL, 0.74 ng/mL and 0.10 ng/ml2 in group 2, respectively. Patient’s age was statistically significant between in two groups (p<0.05). Number of received cores and rate of f/tPSA were 12.24-12 and 20.51-18.45% in group 1 and 2, respectively. tPSA, fPSA and PSA density, number of received cores and rate of f/tPSA were similar in both groups. In group 2, prostate adenocarcinoma was most common detected with Gleason score 3+3 in 19 of 26 patients (73.1%). Conclusions: There is a need different assessment to distinguish of malignant lesions from benign lesions. Nowadays, it was impossible to make this difference in patients without digital rectal examination findings, so accepted threshold of PSA should be 2.5 ng/mL.